Curing Hemoglobinopathies: Challenges and Advances of Conventional and New Gene Therapy Approaches - Motta, Irene (Mediterr J Hematol Infect Dis, 2019)
Inherited hemoglobin disorders, including beta-thalassemia (BT) and sickle-cell disease (SCD), are the most common monogenic diseases worldwide, with a global carrier frequency of over 5%.1 With migration, they are becoming more common worldwide, making their management and care an increasing concern for health care systems. BT is characterized by an imbalance in the α/β-globin chain ratio, ineffective erythropoiesis, chronic hemolytic anemia, and compensatory hemopoietic expansion.1 Globally, there are over 25,000 births each year with transfusion-dependent thalassemia (TDT). The currently available treatment for TDT is lifelong transfusions and iron chelation therapy or allogenic bone marrow transplantation as a curative option. SCD affects 300 million people worldwide2 and severely impacts the quality of life of patients who experience unpredictable, recurrent acute and chronic severe pain, stroke, infections, pulmonary disease, kidney disease, retinopathy, and other complications. While survival has been dramatically extended, quality of life is markedly reduced by disease- and treatment-associated morbidity. The development of safe, tissue-specific and efficient vectors, and efficient gene-editing technologies have led to the development of several gene therapy trials for BT and SCD. However, the complexity of the approach presents its hurdles. Fundamental factors at play include the requirement for myeloablation on a patient with benign disease, the age of the patient, and the consequent bone marrow microenvironment. A successful path from proof-ofconcept studies to commercialization must render gene therapy a sustainable and accessible approach for a large number of patients. Furthermore, the cost of these therapies is a considerable challenge for the health care system. While new promising therapeutic options are emerging,3,4 and many others are on the pipeline,5 gene therapy can potentially cure patients. We herein provide an overview of the most recent, likely potentially curative therapies for hemoglobinopathies and a summary of the challenges that these approaches entail.